Which people should take aspirin for primary prevention of cardiovascular disease? - Lozano R; Franco ME (Dove Medical Press, 2015)
Roberto Lozano,1 Maria-Esther Franco21Pharmacy Department, 2Haematology Department, Hospital Real de Nuestra Señora de Gracia, Zaragoza, SpainDear editorA single trial, ISIS-2,1 in 1988, demonstrated the utility of daily aspirin in the setting of acute myocardial infarction, reducing the risk of vascular death by 23%. In addition, aspirin has also proven effective in the setting of acute ischemic stroke.2 Thus, for a subset of the general population, aspirin may help to prevent heart attacks and strokes. In fact, at low doses, in the range of 75 to 100 mg per day, aspirin prevents the progression of existing cardiovascular disease (CVD), including coronary heart disease, stroke and peripheral arterial disease, and reduces the frequency of cardiovascular events in patients with history of CVD,3,4 referred to as secondary prevention.Although the benefits of aspirin for secondary prevention of CVD are well known, its use in primary prevention of CVD, defined as prevention of the first occurrence of CVD for all patients without clinical CVD, including those with diabetes mellitus and those without clinical evidence of atherosclerotic disease who are at higher CVD risk, is less clear and controversial results have been obtained. In fact, the results of several studies using aspirin for primary prevention of CVD have generally shown more modest reductions of major vascular events compared with secondary prevention (12% vs 23%).3,5